EL HARAKAH : Sabaqa Al-Islaamun Ta'riikhiyyan Wa Tafawwuqihi Fi Irsaa'i Huquuqi Al-Insaani (Diraasatu Muqaaranatin Baina At-Tasyrii'i Al-Islaamiyyi Wa An-Nadzami Al-Wadh'iyyati) - Yusuf Abdullah Musthafa Abdu ar-Razak (UIN Maulana Malik Ibrahim, 2017)
This study covers Islamic low and positive law, which aims to show the role of Islamic in the history of establishing human right.